Novel application of a Fe-Zn double-metal cyanide catalyst in the synthesis of biodegradable, hyperbranched polymers - Sebastian, Joby; Srinivas, Darbha (Chemical Communications, 2011)
The use of Fe-Zn double-metal cyanide as a solid catalyst for synthesizing biodegradable, hyperbranched polymers from diacids and glycerol has been reported, for the first time, wherein acidity, micro-mesoporosity and hydrophobicity of the catalyst played an important role in controlling gelation.

Influence of method of preparation of solid, double-metal cyanide complexes on their catalytic activity for synthesis of hyperbranched polymers - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2013)
Catalytic activity of a series of Fe-Zn double-metal cyanide (DMC) complexes with varying structural and acidic properties has been investigated for the synthesis of hyperbranched polyesters (HPs) from glycerol and succinic acid/adipic acid. The DMC complexes were prepared using different complexing and co-complexing agents. Hydrophobicity of the surface, Lewis acidity and micro-mesoporous architecture are the critical features of DMC enabled control on gelation process in preparing HPs of high degree of branching. The micro-mesoporous architecture of DMC acts as a nano-reactor for reactant molecules to form primary condensation products which further polymerize yielding dendrimers. Hyperbranched polyesters of degree of branching as high as 90% could be achieved without gelation using DMC catalysts. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Dendrimers; Double-metal cyanide; heterogeneous catalysis; Hydrophobic solid acid catalyst; Hyperbranched polymers

Effects of method of preparation on catalytic activity of Co-Zn double-metal cyanide catalysts for copolymerization of CO2 and epoxide - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2014)
Co-Zn double-metal cyanide (DMC) complexes are well-known catalysts for ring-opening polymerization of epoxides and co-polymerization of CO2 and epoxides. This work provides an insight on structure-activity relationship of DMC for poly(cyclohexene carbonate) synthesis. Seven samples of DMC were prepared by different methods and mode of reagent addition. Highly active catalyst could be synthesized even without using a co-complexing agent. CO2 adsorption studies revealed that higher the guest-host interaction higher would be the catalytic activity. High density and strength of Lewis acid sites, moderate crystallinity, low crystal symmetry (rhombohedral/monoclinic), Cl- ions and coordinated tert.-butanol (complexing agent) control the catalytic activity for polycarbonates. Chloride in the structure avoided induction period by increasing acidity of the catalyst and thereby, improving the guest-host interactions. Polycarbonates with CO2 incorporation as high as 86 mol%, average molecular weight of 20900 and polydispersity index of 1.8 were prepared at complete conversion of cyclohexene oxide. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; CO2 utilization; Copolymerization of CO2 and cyclohexene oxide; Double-metal cyanide; Polycarbonate; Structure-activity relationship

Solid, double-metal cyanide catalysts for synthesis of hyperbranched polyesters and aliphatic polycarbonates - Sebastian, Joby; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fe-Zn and Co-Zn double-metal cyanide (DMC) complexes exhibit highly efficient and selective catalytic activity for synthesis of hyperbranched polyesters (glycerol succinic acid (G-SA) and glycerol adipic acid (G-AA)) and aliphatic polycarbonates (via., alternative co-polymerization of cyclohexene oxide and CO2), respectively. The influence of method of preparation of DMC, in particular the mode of addition of reagents, on its physicochemical and catalytic properties was investigated. Co-Zn DMC was found highly selective for polycarbonate (than polyethers) formation. Catalysts prepared using tert-butanol and PEG-4000 as complexing and co-complexing agents, respectively, were found superior to those prepared without these agents. Apart from its role as a coordinating ligand, tert-butanol activated the Lewis acidic Zn2+ sites for reactions in polyester and polycarbonate formation. Hydrophobicity, micro-mesoporosity, acid strength and the amount of coordinated complexing agent are some of the crucial factors influenced the catalytic activity of DMC complexes.
Keywords: aliphatic polycarbonate; CO2 utilization; Double-metal cyanide complex; heterogeneous catalysis; hyperbranched polyester

Factors influencing catalytic activity of Co-Zn double-metal cyanide complexes for alternating polymerization of epoxides and CO2 - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2015)
Co-Zn double-metal cyanides (DMCs) show good catalytic activity towards copolymerization of epoxides and CO2. A deep insight into the structural aspects of the catalysts that control their catalytic performance is addressed in this work. Method of preparation of DMC catalysts was found to have influence on their structure, which in turn dictated their catalytic activity. Complexing agent (t-BuOH) and density of strong acid sites of DMC catalysts were found critical factors responsible for their activity. Selectivity of DMC towards polycarbonates depends on the amount of alkali ion content in their composition. Induction period of the catalysts was governed by the strength of acid sites and by the presence of dispersed ZnCl2 in the composition. This study provides an understanding of the prime features of DMC catalysts that can be tuned for high productivity of polycarbonates. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Copolymerization of epoxides and CO2; Double-metal cyanide; Polycarbonate

Structure-induced catalytic activity of Co-Zn double-metal cyanide complexes for terpolymerization of propylene oxide, cyclohexene oxide and CO2 - Sebastian, Joby; Darbha, Srinivas (RSC Advances, 2015)
The application of Co-Zn double-metal cyanide (DMC) complexes as catalysts for selective terpolymerization of propylene oxide, cyclohexene oxide and CO2 producing polycarbonates is reported for the first time. DMC complexes were prepared with and without using a co-complexing agent. The catalyst with monoclinic/rhombohedral crystal structure and strong Lewis acidity, prepared without using a co-complexing agent showed higher initial activity than that with a cubic structure prepared using a co-complexing agent. Interestingly, no induction period in the terpolymerization reaction was observed. The terpolymer has 75.5 mol% of carbonate fraction in its composition and an average molecular weight of 22 700 and polydispersity index of 2.97. It is characterized by a T-g of 55 degrees C. This structure-induced catalytic activity of DMC can open up new avenues for its applications in other reactions. The influence of process parameters on the catalytic activity of DMC was investigated.